Graphitic carbon nitride based immobilized and non-immobilized floating photocatalysts for environmental remediation. (June 2022) - Rana, Anchal; Sudhaik, Anita; Raizada, Pankaj; Nguyen, Van-Huy; Xia, Changlei; Parwaz Khan, Aftab Aslam; Thakur, Sourbh; Nguyen-Tri, Phuong; Nguyen, Chinh Chien; Kim, Soo Young; Le, Quyet Van; Singh, Pardeep
Abstract: In solar photocatalysis, light utilization and recycling of powder from reaction solution are the main obstructions that hinder the photocatalytic efficacy of any photocatalyst. In this respect, a floatable system is effective for efficient solar photocatalysis by light utilization. Due to the maximum solar light absorption property, floating nanocomposite photocatalyst is an appealing substitute for effective wastewater treatment. Floating photocatalysts are a non-oxygenated and non-stirred solution that is a good light harvester, stable, non-toxic, biodegradable, naturally abundant in nature. They also have low density, a simple preparation process, no need to stir, and high porosity. Due to these characteristics, floating photocatalysts are widely favored and ideal candidates for practical environmental remediation. Several researchers have come up with new and innovative ways for immobilizing capable photocatalyst on a floatable substrate to produce floating nanocomposite photocatalytic material. In recent decades, g–C3 N4 –based floating photocatalysts have gained a lot of attention as g-C3 N4 is a visible light active photocatalyst with unique and exceptional properties. It also has good photocatalytic activity in waste water treatment and environmental remediation. Many previous reports have studied the logical design and manufacturing method for heterojunction floating photocatalysts and immobilized floating photocatalysts. Based on those studies, we have focused on the g-C3 N4 based immobilized and non-immobilized floating photocatalysts for pollutant degradation. We have also categorized immobilized floating photocatalyst based on several lightweight substrates such as expanded perlite and glass microbead. In addition, future challenges have been discussed to maximize solar light absorption and to improve the efficiency of broadband response floating photocatalysts. Floating photocatalysis is an advanced technique in energy conversion and environmental remediation thus requires special consideration. Graphical abstract: Image 1 Highlights: Floating photocatalysis and immobilization were discussed. Role of floating photocatalysts have been briefly explicated. Different immobilized and non-immobilized materials were explained. Photocatalytic applications of g-C3N4 based floating photocatalysts were described. Current challenges with future viewpoints were elucidated.